The Effects of Inflation, Exchange Rate, and Import on Value Added Tax and Sales Tax of Luxury Goods - Bambang Subiyanto; Tiara Pradani; Kumba Digdowiseiso; Nada Virgita (Budapest International Research and Critics University, 2022)
This study aims to examine the effects of inflation, exchange rate, and import on value added tax (PPN) and sales tax of luxury goods (PPnBM) over the period 2016-2020. This type of research is quantitative using the purposive sampling technique. Based on the predetermined criteria, a sample of external macroeconomic indicators that are subject to PPN and PPnBM is selected in 2016-2020. The results of this study indicated that both inflation and exchange rate had no significant effect on value added tax and sales tax of luxury goods. In contrast, import produced a positive and significant effect on value added tax and sales tax of luxury goods.